Digging Lincoln An archaeological memoir - Jones, Michael John 1938- (Archaeopress, 2024)
A uniquely personal account of how a record of the city of Lincoln's rich archaeology was recorded from the time of the early antiquaries through to the commercially funded professional teams of today, by someone who was closely involved in a senior capacity for over half a century.